The Influence of Product Quality, Trust, and Service Quality on Consumer Satisfaction: (Study of Vivan Robot Product Users in Jakarta) - Agus Sriyanto; Riko Ulanda (International Journal of Management Research and Economics, 2024)
To find out the influence of product quality which partially influences consumer satisfaction, to find out the influence of trust which partially influences consumer satisfaction, to find out the influence of service quality which partially influences consumer satisfaction of Vivan robot product users in Jakarta. The population in this research are consumers who visit and purchase Vivan Robot products in DKI Jakarta, both individuals and shops. The exact number of population members is not known. The number of samples in this study was 96 respondents. The results of the observations that have been obtained are the product quality. partially has a significant effect on Consumer Satisfaction, Trust partially has a significant effect on Consumer Satisfaction, Service Quality partially has a significant effect on Vivan Robot Consumer Satisfaction.